Pengaruh Pemberian Tambahan Penghasilan Pegawai (TPP) dan Motivasi Kerja terhadap Kinerja Guru (Studi pada Dinas Pendidikan Kabupaten Merauke) - Balagaize, Yohana Erviana (LPPM Institut Pendidikan Nusantara Global, 2025)
The purpose of this study is to examine and analyze the influence of the Provision of Employee Income Allowances (TPP) and Work Motivation on Teacher Performance at the Department of Education in Merauke Regency, both individually and jointly. This study uses a quantitative research approach by applying statistical analysis to assess the extent of the relationship between the independent variables, namely income allowances and motivation, and the dependent variable, which is teacher performance. The results show that both income allowances and work motivation have a positive and significant effect on teacher performance. When assessed individually, each factor contributes meaningfully to enhancing performance. However, when analyzed together, their combined effect is more pronounced. This indicates that an appropriate balance between financial support and strong work motivation can create a supportive and productive working environment. Such a condition is vital in improving the effectiveness and quality of the learning process. In public institutions like the Department of Education, these findings underline the importance of designing policies that not only provide sufficient financial incentives but also foster intrinsic motivation among educators. The presence of fair compensation and a motivating work atmosphere encourages teachers to be more committed, responsible, and effective in carrying out their duties. This study concludes that efforts to improve teacher performance must consider both financial and non-financial aspects to achieve sustainable improvements in educational outcomes and service quality.